The Contribution of Cortical Lesions to a Composite MRI Scale of Disease Severity in Multiple Sclerosis - Yousuf, Fawad; Kim, Gloria; Tauhid, Shahamat; Glanz, Bonnie I.; Chu, Renxin; Tummala, Subhash; Healy, Brian C.; Bakshi, Rohit (Frontiers in Neurology, 2016)
Objective: Test a new version of the Magnetic Resonance Disease Severity Scale (v.3 = MRDSS3) for multiple sclerosis (MS), incorporating cortical gray matter lesions (CLs) from 3T MRI. Background: MRDSS1 was a cerebral MRI-defined composite scale of MS disease severity combining T2 lesion volume (T2LV), the ratio of T1 to T2LV (T1/T2), and whole brain atrophy (brain parenchymal fraction-BPF). MRDSS2 expanded the scale to include cerebral gray matter fraction (GMF) and upper cervical spinal cord area (UCCA). We tested the contribution of CLs to the scale (MRDSS3) in modeling the MRI relationship to clinical status. Methods: We studied 51 patients [3 clinically isolated syndrome, 43 relapsing-remitting, 5 progressive forms, age (mean±SD) 40.7±9.1 years, Expanded Disability Status Scale (EDSS) score 1.6±1.7]and 20 normal controls by high-resolution cerebrospinal MRI. CLs required visibility on both fluid-attenuated inversion-recovery (FLAIR) and modified driven equilibrium Fourier transform (MDEFT) sequences. The MACFIMS battery defined cognitively impaired (n=18) vs. preserved (n=33) MS subgroups. Results: EDSS significantly correlated with only BPF, UCCA, MRDSS2 and MRDSS3 (all p<0.05). After adjusting for depressive symptoms, the cognitively impaired group had higher severity of MRI metrics than the cognitively preserved group in regard to only BPF, GMF, T1/T2, MRDSS1 and MRDSS2 (all p<0.05). CL number was not significantly related to EDSS score or cognition status. Conclusions: CLs from 3T MRI did not appear to improve the validity of the MRDSS. Further studies employing advanced sequences or higher field strengths may show more utility for the incorporation of CLs into composite scales.